Neurotensin and its receptors in the control of glucose homeostasis - Mazella, Jean; Béraud-Dufour, Sophie; Devader, Christelle; Massa, Fabienne; Coppola, Thierry (Frontiers in Endocrinology, 2012)
The pharmacological roles of the neuropeptide neurotensin through its three known receptors are various and complex. Neurotensin is involved in several important biological functions including analgesia and hypothermia in the central nervous system and also food intake and glucose homeostasis in the periphery. This review focuses on recent works dealing with molecular mechanisms regulating blood glucose level and insulin secretion upon neurotensin action. Investigations on crucial cellular components involved in the protective effect of the peptide on beta cells are also detailed. The role of xenin, a neurotensin-related peptide, on the regulation of insulin release by glucose-dependent insulinotropic polypeptide is summarized. The last section comments on the future research areas which should be developped to address the function of new effectors of the neurotensinergic system in the endocrine pancreas.